The Influence of Sex Appeal on Consumers Attitude toward the Ads Moderated by Product Factors - Nusantara, Aji Cahya; Haryanto, Budhi (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2018)
This study wants to examine the relationship between sex appeal and attitude towards the ads, and more than, this study also wants to examine the role of product factors in moderating the relationship of this two variables. Experimental design is done to control the relation among the variables observed in this study. The participants consist of 100 males’ undergraduate students of Faculty of Economics and Business, Universitas Sebelas Maret, Surakarta-Indonesia, who are divided into 4 groups. Generalized Auto Regression Conditional Hetero-regressive (GARCH) is statistical method chosen to analysis the data. The results showed that sex appeal is an effective stimulus affects the individual positive attitude toward an advertisement. As well as product factor is another stimulus, which effectively influence positive attitudes toward advertising. But in this study also found that the product factor is not moderate the relationship between sex appeal and positive attitude toward advertising. In addition to this study also discusses the implications of both theoretical and practical, as well as the limitations of the study.